Community Based Tourism in the Neoliberal City? Reflections from a “slum area” in Buenos Aires - Triana Sánchez Attanasio (Via@)
This paper analyzes a government project called “Urban Community Tourism” that aimed to bring two working-class neighborhoods in the City of Buenos Aires closer to tourism activity. Based on the case of Rodrigo Bueno, it is evident how the image of the neighborhood has been shaped by official discourses that oscillate between stigmatization and idealization, with underlying political and economic interests typical of a neoliberalised city. Although the government plan promotes community participation, the practices observed suggest limited local agency. The research highlights the importance of analyzing the impacts perceived by the population and of recognizing the capacity of local actors to define their own tourism future. It is concluded that the success of community tourism in Rodrigo Bueno will depend on the extent to which a balance is achieved between external initiatives and active community participation.